Interplay between Philosophical Orientation and Musical Literacy Index of English as a Foreign Language (EFL) Teachers - Estremera, Michael E; Gonzales, John T (ASEAN Multidisciplinary Research Journal, 2021)
Teachers’ philosophy of education guides their behavior or performance in the classroom. The philosophy statement reflects their personality and values. To highlight the intervening variables of the study, the researcher deemed mixed method of research appropriate. The quantitative aspect involves the use of correlation statistical tool while the qualitative aspect pertains to the use of the verbatim and transcribed interviews. To quantify and establish correlations between the educational philosophy orientations and musical literacy index of EFL music teacher participants, Pearson correlation was used. One supposition confirmed by this study is the paramount influence of educational philosophies in the pedagogical practice of EFL music teachers. The orientations serve as a guide to thread the right direction considering the goals and visions of the Department of Education (DepEd). The noteworthy relationships between variables may presuppose that there is a perceived room for improvement in the pedagogical practice and musical literacy of EFL music teachers to cater to the 21st century learning needs of the clienteles. The current study suggests that there is a need to practically unravel the plights of the EFL participants along instructional materials inadequacies, mismatch of trainings, and language of instruction issue, to be able to establish a sound school climate conducive to learning. Trainings must also be conducted to enhance the musical literacy of EFL teachers.